2021
DOI: 10.3390/microorganisms9030604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inclusion of Fermented Mulberry Leaves and Branches in the Gestational Diet on the Performance and Gut Microbiota of Sows and Their Offspring

Abstract: Fermented feed mulberry (FFM), being rich in dietary fiber, has not been fully evaluated to be used in sow’s diet. In this study, we investigated the effects of 25.5% FFM supplemented gestation diets on the performance and gut microbiota of sows and their offspring. Results showed that the serum concentration of glucose, progesterone, and estradiol were not affected by the dietary treatment, while the level of serum insulin and fecal short chain fatty acid were both reduced in FFM group on gestation day 60 (G6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…In addition to reducing body weight losses, the metabolism and immune changes in sows during pregnancy and lactation also affect the growth of piglets; increasing sow lactation feed intake maintains body condition and milk production, which directly improves reproductive performance ( 37 , 38 ). Previous studies have shown that dietary fiber supplementation not only promotes satiety in sows but also improves sow feed intake during lactation ( 12 , 34 , 39 ). In the present study, we found that the addition of different levels of FBF to the diet of sows in late gestation and lactation affected the performance of both sows and piglets, with 4% FBF in particular significantly increasing ADFI in sows and weaning weight in piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing body weight losses, the metabolism and immune changes in sows during pregnancy and lactation also affect the growth of piglets; increasing sow lactation feed intake maintains body condition and milk production, which directly improves reproductive performance ( 37 , 38 ). Previous studies have shown that dietary fiber supplementation not only promotes satiety in sows but also improves sow feed intake during lactation ( 12 , 34 , 39 ). In the present study, we found that the addition of different levels of FBF to the diet of sows in late gestation and lactation affected the performance of both sows and piglets, with 4% FBF in particular significantly increasing ADFI in sows and weaning weight in piglets.…”
Section: Discussionmentioning
confidence: 99%
“…and Bifidobacterium spp. Both polyphenolic compounds and fiber content or type, soluble or insoluble, included in the diet can affect the intestinal microbiota composition of animals [ 34 , 35 ]. Regarding fiber type, there is rising evidence for a helpful growth upgrade, such as lactobacilli and bifidobacteria in the small intestine of pigs, through inclusion of some dietary fiber types, such as insoluble fiber [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have explored the effects of different types of FF on animal growth performance, immunity, intestinal (f) 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0% % % % % % % % % % % % % % % FF FF FF FF FF FF FF FF FF FF FF FF FF FF FF health and animal products quality. Some of these studies have found that fermented Chinese herbal medicine (22) , fermented maize germ meal (23) , mulberry leaves (24) and fermented mixed feed (25,26) have positive effects on pig husbandry. However, the effects of FF based on maizesoyabean meal-wheat bran on muscle fibre types and muscle lipid composition in finishing pigs remain unclear.…”
Section: Discussionmentioning
confidence: 99%